Stereotactic Radiosurgery and Hypofractionated Stereotactic Radiotherapy for Nonfunctioning Pituitary Adenoma - Khattab, Mohamed H.; Sherry, Alexander D.; Xu, Mark C.; Kelly, Patrick; Anderson, Joshua L.; Luo, Guozhen; Chambless, Lola B.; Cmelak, Anthony J.; Attia, Albert (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objectives Hypofractionated stereotactic radiotherapy (HSRT) in two to five fractions may offer patients with large nonfunctioning pituitary adenomas (NFPAs) with chiasm involvement a safe and effective treatment over a single week. However, little has been reported regarding this novel approach.Design We compared the feasibility, outcomes, and toxicity of single-fraction stereotactic radiosurgery and HSRT.Setting This study was conducted at a tertiary academic referral center.Participants After approval by the institutional review board, we performed a retrospective cohort study of patients treated at our institution with stereotactic radiosurgery (SRS) and HSRT for NFPA. Selection for SRS or HSRT was based on clinicopathologic factors including tumor size and cavernous sinus invasion at the discretion of the treating physician.Main Outcome Measures Local control, endocrinopathy, and radiation-associated toxicity were evaluated by binary logistic regression and Cox's proportional hazards regression.Results A total of 45 patients with mean follow-up of 5 years were enrolled including 26 patients treated by HSRT with mean follow-up of 3 years and 19 patients treated by SRS with median follow-up of 6 years. Clinicopathologic characteristics were balanced between cohorts. Local failure at last follow-up was 5% in the SRS cohort and 8% in the HSRT cohort, and rates of post-SRS endocrinopathy were similar between each cohort. Late complications including radionecrosis, visual deficit, and secondary malignancy were minimal in either cohort.Conclusions HSRT is an appropriate treatment strategy for patients with NFPAs, particularly for optic pathway preservation in the setting of large tumors with chiasm involvement. Further studies are needed to optimize fractionated approaches and patient selection.
Keywords: Hypofractionated Stereotactic Radiotherapy; stereotactic radiosurgery; non-functioning pituitary adenoma; fractionation; toxicity